High pressure processing as an alternative food preservation technology and its applications for fruits and vegetables. - Abdel Karim, Pia (Kansas State University, 2011)
Consumers demand for high quality, natural and fresh tasting food, free from preservatives and additives, with a clean label and an extended shelf life has increased. High pressure processing (HPP), also known as high hydrostatic pressure, is a non-thermal food preservation technique that has the potential to meet these demands. It is an opportunity to preserve food, by applying intensive pressure in the range of 300-900 MPa, without adversely affecting organoleptic, textural and nutritional qualities as thermal processing like pasteurization and sterilization may do. In a typical high pressure batch cycle, the food prepackaged in a high-barrier flexible pouch or a plastic container is loaded into a perforated basket that goes into the pressure vessel; the pressure is then increased to the processing target pressure (come-up time); the product is held at the desired pressure for 3 to 10 minutes (pressure holding time); after which the pressure is released in usually few seconds (decompression time) and the product can be unloaded at this point. The pressure is applied uniformly in all directions simultaneously and this is known as isostatic pressure. Pressurization is usually accompanied by a moderate and uniform temperature increase called adiabatic heating. However, the food product usually rapidly returns to its initial temperature at decompression. With the recent shift in consumer lifestyle toward healthy living and healthier food, the consumption of raw fruits and vegetables has increased in popularity. However, as per the Centers of Disease Control and Prevention, fruits and vegetables have recently been associated with multiple foodborne disease outbreaks; the effect of high pressure processing on microbial safety, quality and sensory characteristics of fruits and vegetables has therefore been widely investigated as an alternative to traditional food processing and preservation methods. HPP inactivates microorganisms and quality-deteriorating enzymes and has limited effects on covalent bonds resulting in minimal modifications of food-quality attributes such as color, flavor and nutritional values. However, depending on the fruit or vegetable, high pressure could induce chemical or biochemical reactions that can affect their quality attributes.
Keywords: High pressure processing; Food Science (0359)